(untitled) (Bhartiya Knowledge Systems, 2024)
The author has taken a keen interest in reviving back the best techniques of the Teaching-Learning process of ancient India. In doing this, Chanakya’s best mantras were borrowed. The paper speaks of the beauty of teaching-learning practices uniquely existed during ancient times. The best mantras included Prayer, Thinking Process, Time-Table, Self-Study and Continuous Learning. These are not unique terms, only the shape given to these components by Chanakya has its own uniqueness. Tracing the history, Chanakya was found to stress on the significance of prayer as a part of teaching-learning process. It is not necessarily a feature of teaching-learning practice of the contemporary formal education system. Chanakya saw prayer as a strong force for building good relationships between teachers and the students, igniting love and respect for each other. Regarding the thinking process, Chanakya talked about five aspects of thinking which include, logical thinking, reasoning, scientific thinking, strategic thinking, and critical thinking. He put emphasis on the correct thinking process in the light of displaying characteristics of both science and art. Another mantra according to Chanakya was preparation of a perfect time-table, a time-table which works best for the individual. To him, planning the work was important to begin with preparing a time-table. Self –study is another mantra designed, specifically for three phases. First, study from textbooks/scriptures by the self. Second, hearing and understanding from the teachers. Finally, achieving of the self-reflection or thought processing. In addition, the idea of continuous learning is visible even in the contemporary scene. The difference is when Chanakya guided his students towards development of learning habits such as teacher-like thinking, going beyond the interest area, traveling to new places, being curious, and the writing practices.